Dark matter from torsion in Friedmann cosmology - Pereira, S. H. [UNESP]; Vicente, A. M. [UNESP]; Jesus, J. F. [UNESP]; Holanda, R. F. L. (Springer Nature, 2022)
A cosmological model in an Einstein–Cartan framework endowed with torsion is studied. For a torsion function assumed to be proportional to Hubble expansion function, namely ϕ= - αH, the contribution of torsion function as a dark matter component is studied in two different approaches. In the first one, the total matter energy density is altered by torsion coupling α, giving rise to an effective dark matter and cosmological constant terms that reproduce quite well the flat cosmic concordance model. In the second approach, starting with just standard baryonic matter plus a cosmological constant term, it is obtained that the coupling of torsion with baryons and cosmological constant term naturally gives rise to a dark matter contribution, together a modified cosmological term. In this model the dark matter sector can be interpreted as an effective coupling of the torsion function with the ordinary baryonic matter and cosmological constant. Finally, it is shown that both models are totally compatible with recent cosmological data from Supernovae and Hubble parameter measurements.